A Prospective Study of Dry Eye in Patients after Manual Small Incision Cataract Surgery - Ekanksha Kanfade1 , Chetan Saoji2 , Sachin Daigavane3 , Sonal Muley4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Dry eye is a multifactorial disease of the tears and ocular surface with symptoms of discomfort,visual disturbance, etc. with potential damage to the ocular surface. Additionally, it is followed by increasedtear film osmolarity and ocular surface inflammation. Schirmer’s I and tear film breakup time is performedto determine the dryness level as mild, moderate, and severe.Aim : The research aims to establish the incidence of dry eye in patients after small incision cataract surgery.Material and Method: 100 patients who met inclusion criteria were enlisted for cataract surgery. Everypatient was asked about symptoms related to dry eye and then they underwent Schirmer’s test 1 and tear filmbreakup time test. After this, patients were subjected to surgery with a 6-7 mm superior incision. On 1st, 7thand 30th day after operation schirmer’s and tear film breakup time test was again performed. The dryness ofthe eyes was then analysed and graded in accordance with the 2007 DEWS classification.Result: Out of 100 samples, 16% had dry eye preoperatively which increased to 89% postoperatively on 1stday. Out of these 89 patients having dry eye postoperatively, 35 were male and 54 were female. Gradually itreduced after 7th day and 30th day postoperatively. The mean age of the patients was 66.15 years with SD6.10. The schirmer’s test I and tear film breakup time p values were clinically significant< 0.0001.Conclusion: After manual small incision cataract surgery, moderate to severe dryness was observed. Thisdryness stabilized gradually after 1st week of surgery and improved significantly further after one monthwith the use of lubricants, antibiotic and steroid combination.